Medios tecnológicos (celular e internet) y la educación sexual en los estudiantes de la Unidad Educativa Dr. Segundo Wong Mayorga - Santi Loor, Alex Iván (2019)
The present work has as property, to establish the incidence of technological means (cellular and internet) in sexual education, clarifying doubts, clearing fears about the use and application that can be given to these resources, to refer to sexuality and conceiving a healthy personality, autonomous of imaginary affirmations and convenient at the time of valuing the body, like beginning of own happiness and its social and familiar surroundings. The requirement of teaching sexual education in educational institutions must be guaranteed to children and adolescents through the school curriculum since over the years the importance of a sexual education has been treasuring value and has consented to raise awareness by taking such responsibility in a systematic, equitable, profound, authentic and related manner. The question based on the subject is unquestionable, since sex education is installed in the concurrence of phenomena that move away innovations in modern societies. The teaching of Sexual Education is formed first in the integral element of an individual established in thought and then that they absorb all the biological, psychological, and spiritual information, so that responsible parenthood is the culmination of their efforts. In addition, this work will help to use technological means as basic resources to effectively socialize the issue of sexuality. There are many reasons why Sex Education is integrated into curricula to involve both students and teachers and parents in the same common project.